Active Antialopecia Chemical Identification of Merremia peltata Leaves and Computational Study toward Androgen Receptor Using Molecular Docking and Molecular Dynamic Simulation - Syawal Abdurrahman; Ruslin Ruslin; Aliya N. Hasanah; Resmi Mustarichie; Mus Ifaya (The Scientific World Journal)
Alopecia is a health condition in which the hair loses its function in some or all of the body. Alopecia occurs due to various genetic, environmental, and nutritional factors. One of the methods developed to treat alopecia is through inhibition of the enzyme 5-α-reductase, which converts testosterone into its more potent metabolite, dihydrotestosterone (DHT). In ethnomedicine, the leaves of Merremia peltata are used by the people of Sulawesi as a remedy for baldness. Therefore, in this study, an in vivo study was conducted on rabbits to investigate the antialopecia activity of the ethanolic extract of M. peltata leaves. The purified M. peltata leaf extract was fractionated using vacuum liquid chromatography with several solvents to produce fractions F1–F5. Each fraction was then retested in vivo in rabbits, and its content was then analyzed by LC-MS. An in silico study was then carried out using minoxidil as a comparison ligand; 17 compounds derived from M. peltata leaves were identified as antialopecia compounds through prediction of molecular interactions and molecular dynamics simulation and prediction of absorption, distribution, metabolism, excretion, and toxicology (ADME-Tox). The assay results showed that fractions F2 and F3 had a better effect on hair growth compared to the positive control, and the test compound obtained from the LC-MS analysis, bufotalinin, had a strong binding energy to the receptor in the molecular docking interaction study: −5.99 kcal/mol compared to −4.8 kcal/mol for minoxidil. Molecular dynamics simulation analysis with complex stability parameters based on solvent-accessible surface area (SASA), principal component analysis (PCA), root mean square deviation (RMSD), and root mean square fluctuation (RMSF) showed that bufotalinin has good affinity for androgen receptors. ADME-Tox prediction for bufotalinin showed good results for the parameters of skin permeability, absorption, and distribution. Therefore, bufotalinin, a steroid compound, is a potential androgen receptor antagonist and could be useful in the treatment of alopecia.